Morphologic, cytometric, quantitative transcriptomic and functional characterisation provide insights into the haemocyte immune responses of Pacific abalone (Haliotis discus hannai) - Ma, Zeyuan; Wu, Yunlong; Zhang, Yu; Zhang, Weini; Jiang, Mingmei; Shen, Xiaoyue; Wu, Hailian; Chen, Xinhua; Di, Guilan (Frontiers in Immunology, 2024)
In recent years, the abalone aquaculture industry has been threatened by the bacterial pathogens. The immune responses mechanisms underlying the phagocytosis of haemocytes remain unclear in Haliotis discus hannai. It is necessary to investigate the immune mechanism in response to these bacterial pathogens challenges. In this study, the phagocytic activities of haemocytes in H. discus hannai were examined by flow cytometry combined with electron microscopy and transcriptomic analyses. The results of Vibrio parahaemolyticus, Vibrio alginolyticus and Staphylococcus aureu challenge using electron microscopy showed a process during phagosome formation in haemocytes. The phagocytic rate (PP) of S. aureus was higher than the other five foreign particles, which was about 63 %. The PP of Vibrio harveyi was about 43%, the PP peak of V. alginolyticus in haemocyte was 63.7% at 1.5 h. After V. parahaemolyticus and V. alginolyticus challenge, acid phosphatase, alkaline phosphatase, total superoxide dismutase, lysozyme, total antioxidant capacity, catalase, nitric oxide synthase and glutathione peroxidase activities in haemocytes were measured at different times, differentially expressed genes (DEGs) were identified by quantitative transcriptomic analysis. The identified DEGs after V. parahaemolyticus challenge included hemagglutinin/amebocyte aggregation factor-like, supervillin-like isoform X4, calmodulin-like and kyphoscoliosis peptidase-like; the identified DEGs after V. alginolyticus challenge included interleukin-6 receptor subunit beta-like, protein turtle homolog B-like, rho GTPase-activating protein 6-like isoform X2, leukocyte surface antigen CD53-like, calponin-1-like, calmodulin-like, troponin C, troponin I-like isoform X4, troponin T-like isoform X18, tumor necrosis factor ligand superfamily member 10-like, rho-related protein racA-like and hemagglutinin/amebocyte aggregation factor-like. Some immune-related KEGG pathways were significantly up-regulated or down-regulated after challenge, including thyroid hormone synthesis, Th17 cell differentiation signaling pathway, focal adhesion, melanogenesis, leukocyte transendothelial migration, inflammatory mediator regulation of TRP channels, ras signaling pathway, rap1 signaling pathway. This study is the first step towards understanding the H. discus hannai immune system by adapting several tools to gastropods and providing a first detailed morpho-functional study of their haemocytes.